Income Distribution and Increase in Production Using Social Accounting Matrices - Ali Asghar Banouei (فصلنامه پژوهش‌های اقتصادی ایران, 2005)
The main focus of this article is to estimate production and household income multipliers for seven sectors of the economy using the four Iranian Social Accounting Matrices(1970, 1973, 1996 and 2000). The results show that the impact of policies of sectoral expansions generate household income inequalities and is expected to continue in the future. However, it is observed that agriculture and agro-based industries do have positive impact on the development of the economy, but fail to guarantee the urban-rural household income equalities which seems to be an unavoidable phenomenon for the Iranian economy. The results are based on current prices and therefore, the estimation of social accounting matrices in constant prices would better portray the structure of the economy.